Model and data engineering 2nd international conference, MEDI 2012, Poitiers, France, October 3-5, 2012. Proceedings - Bellatreche, Ladjel; Benatallah, Boualem; Abelló, Alberto (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 2nd International Conference on Model and Data Engineering, MEDI 2012, held in Poitiers, France, in October 2012. The 12 revised full papers presented together with 5 short papers were carefully reviewed and selected from 35 submissions. The papers are cover the topics of model driven engineering, ontology engineering, formal modeling, security, and data mining.